Flexibility strategies and their relationship with workplace environment, dedication and intellectual challenge - Madero-Gómez, Sergio (Universidad Autónoma de Tamaulipas, 2021)
Currently, there are many companies in the world that have been integrating flexibility strategies as an important part in the human resources processes, mainly as an additional component of their emotional salary. The aim of this research is to understand the correlation between job flexibility and dedication, intellectual challenge and the work environment that people perceive in their workplace. A quantitative research was carried out during November 2018. An online questionnaire of 38 items was administered to a sample of 282 Mexican workers from the city of Monterrey, Nuevo León in Mexico. Findings indicate that 95.4 % of interviewees showed an interest for at least one of the flexible work variants. The open space work modality was the least desirable with a 7.8 % preference. A positive correlation between work environment and a positive balance due to flexible work was found. The working environment similarly showed a high positive correlation with dedication and intellectual challenge. The foregoing findings are of interest to the current context for human resource strategies and the business environment.